Analisis Penggunaan Bolus Berbahan Plastisin pada Pasien Fibrosarcoma dengan Treatment Planning System (TPS) - Riska Fitriani; Kadek Subagiada; Suhadi Muliyono; Robert Janssen Stevenly; Suryaningsih Suryaningsih (Program Studi Fisika, Jurusan Fisika, FMIPA, Universitas Mulawarman, 2022)
Bolus is a material that has properties similar to body tissues and is used to maximize the absorbed dose on the skin surface. The purpose of this research was to determine the most optimal treatment to kill fibrosarcoma on the patient’s skin surface by comparing the isodose curve and the value of the radiation absorption dose on the physical bolus (from CT-Scan) and model bolus (TPS). This study used data in the form of bolus images (with a bolus thickness of 0 cm, 0.5 cm and 1.0 cm) and phantom image. Then the data was processed with Treatment Planning System (TPS) and given energy variations in the form of electrons (10 MeV, 12 MeV, dan 15 MeV) and photons (6 MV and 10 MV). The result of this research was an isodosis curve that describes the distribution of the dose and the value of the absorbed dose of radiation received by the skin surface. The conclusion of this research is a bolus thickness of 0,5 cm and an electron energy of 15 MeV, has more even isodose curve (covering the entire tumor) and the maximum absorption dose value were 5720 cGy for physical bolus and 5710 cGy for TPS bolus.